Efforts to Improve Teachers’ Competence in the Use of Learning Models - Iis Haerunisa; Suhanda Suhanda (PT. Anagata Sembagi Education, 2026)
Teachers’ competence in selecting and implementing appropriate learning models is essential to improve the quality of classroom instruction. However, preliminary observations at SMP Negeri 4 Baradatu indicated that teachers’ ability to apply learning models was not yet optimal and learning practices tended to remain teacher-centered. This study aimed to improve teachers’ competence in the use of learning models through training activities within a School Action Research framework. This research employed a two-cycle School Action Research design involving 20 teachers. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected using a questionnaire based on competency indicators, including understanding learning model concepts, selecting appropriate models, explaining syntax, adjusting time allocation, determining media and learning resources, and aligning assessment strategies. Data were analyzed using descriptive quantitative techniques by calculating percentage scores for each indicator and overall averages. The results showed that teachers’ average competence increased from 72% in Cycle I (sufficient category) to 81% in Cycle II (good category). Significant improvements were observed particularly in explaining model syntax and selecting models appropriate to teaching materials. The findings indicate that reflective practice within the action research cycle contributed to continuous professional improvement. In conclusion, training integrated with School Action Research effectively enhanced teachers’ competence in implementing learning models and promoted sustainable professional development.